Influence Human Development Index, Open Unemployment Rate, and Product Gross Regional Domesticity Per Capita on Poverty in Indonesia - Umara, Gharas; Gunarto, Toto; Yuliawan, Dedy (Revenue Journal: Management and Entrepreneurship, 2024)
Poverty problem has become a problem in societies and countries in this world. Indonesia continues to try to get out of the poverty zone, and the government at the central and regional levels is carrying out various efforts and programs to lower poverty in Indonesia. This research was conducted to see the influence of human development index (HDI) data, unemployment rate open (TPT), and GDP per capita of 34 Provinces in Indonesia on the Number of Poor populations of 34 Provinces in Indonesia in 2022. This research uses a quantitative method with a descriptive approach. The data source in this research is secondary data from the Central Statistics Agency (BPS) in the form of data on the number of poor people in 34 provinces in Indonesia, and data on 34 provinces in Indonesia human development index (HDI), unemployment rate open (TPT), and GDP per capita originate from the Central Statistics Agency (BPS). All research results, which are variable independent in this study, have a simultaneous relationship with the number of poor people. The Human Development Index (HDI) is negative and significant in a way statistics on the number of poor people, the open unemployment rate (TPT) has an influence positive and essential in a way statistics on the number of poor people and GDP per capita influential negative and significant in a way statistical to the total poor population.